Effects of Oral Lycopene Supplementation on Vascular Function in Patients with Cardiovascular Disease and Healthy Volunteers: A Randomised Controlled Trial - Gajendragadkar, Parag R.; Hubsch, Annette; Mäki-Petäjä, Kaisa M.; Serg, Martin; Wilkinson, Ian B.; Cheriyan, Joseph (PloS one, 2014)
The mechanisms by which a 'Mediterranean diet' reduces cardiovascular disease (CVD) burden remain poorly understood. Lycopene is a potent antioxidant found in such diets with evidence suggesting beneficial effects. We wished to investigate the effects of lycopene on the vasculature in CVD patients and separately, in healthy volunteers (HV). We randomised 36 statin treated CVD patients and 36 healthy volunteers in a 2∶1 treatment allocation ratio to either 7 mg lycopene or placebo daily for 2 months in a double-blind trial. Forearm responses to intra-arterial infusions of acetylcholine (endothelium-dependent vasodilatation; EDV), sodium nitroprusside (endothelium-independent vasodilatation; EIDV), and NG-monomethyl-L-arginine (basal nitric oxide (NO) synthase activity) were measured using venous plethysmography. A range of vascular and biochemical secondary endpoints were also explored. EDV in CVD patients post-lycopene improved by 53% (95% CI: +9% to +93%, P = 0.03 vs. placebo) without changes to EIDV, or basal NO responses. HVs did not show changes in EDV after lycopene treatment. Blood pressure, arterial stiffness, lipids and hsCRP levels were unchanged for lycopene vs. placebo treatment groups in the CVD arm as well as the HV arm. At baseline, CVD patients had impaired EDV compared with HV (30% lower; 95% CI: -45% to -10%, P = 0.008), despite lower LDL cholesterol (1.2 mmol/L lower, 95% CI: -1.6 to -0.9 mmol/L, P<0.001). Post-therapy EDV responses for lycopene-treated CVD patients were similar to HVs at baseline (2% lower, 95% CI: -30% to +30%, P = 0.85), also suggesting lycopene improved endothelial function. Lycopene supplementation improves endothelial function in CVD patients on optimal secondary prevention, but not in HVs. ClinicalTrials.gov NCT01100385.